The effects of temperature on wear behaviours of Al-Cu alloy and Al-Cu/SiC composite - Muratoglu, M; Aksoy, M (Elsevier Science Sa, 2000)
The friction and wear behaviour of 2124 aluminum alloy and 25 vol.% SiC reinforced 2124 aluminum alloy composite which are produced by powder metallurgy method, against AISI 1050 steel were investigated in a block-on-ring apparatus at different temperatures. Sliding wear tests were conducted at 2 ms(-1) velocity. Dry sliding tests and lubricated sliding tests were performed under the loads of 52 and 312 N, respectively. Some of the wear tests were carried out with artificially aged specimens in order to determine the aging effect. On the other hand, some specimens were subjected to heating in the temperature intervals of 25-200 degrees C and wear tests were performed to determine the effects of test temperature on wear behaviours of the composite and the matrix material. It has been found that 100 degrees C were a transition temperature for wear rate and wear mechanisms for dry sliding tests. It was also observed that, below 100 degrees C, aged specimens of both the composite and matrix material indicated higher wear rate with a mild abrasive wear mechanism than that of nonaged specimens of them. However, nonaged specimens of both the composite and matrix material showed higher wear rate with severe adhesive wear mechanism than that of aged specimens of them above 100 degrees C. Metallographic subsurface observations of test samples indicated that the highest wear resistance was obtained with the deepest plastic deformation zone. For the tests performed at 25 degrees C (RT), the wear rate of the composite material under dry sliding condition was higher than that of the lubricated sliding condition. (C) 2000 Elsevier Science S.A. All rights reserved.
Keywords: wear behaviour; Al-Cu/SiC composite; 2124 aluminum alloy